Microprocessor-Based System for Monitoring Spinal Evoked Potentials During Surgery - Gopalan, Ramachandran; Parker, Philip A.; Scott, Robert N. (IEEE transactions on biomedical engineering, 1986)
Recently there has been considerable interest in the use of evoked potentials for monitoring the functional integrity of the spinal cord during surgical procedures such as spinal fusion. This paper describes a signal processing regimen consisting of ensemble averaging and matched filtering, developed to enhance the signal-to-noise ratio of surface-recorded spinal evoked potentials. This system also allows reliable detection of changes in signal latency, amplitude, and waveshape, the main parameters of interest. A microprocessor-based dedicated system for collection and processing of somatosensory evoked potentials data on-line has been designed. Portability, cost effectiveness, and user interaction aresome of the main characteristics of the system design. The performance of the system has been evaluated in the laboratory with simulated data, and data recorded from human subjects. The system performance meets the design expectations. Arrangements are being made to evaluate the system in the clinical environment.